Relationship-based practice and the creation of therapeutic change in long-term work: social work as a holding relationship. Issue 2 (17th February 2022) - Ferguson, Harry; Warwick, Lisa; Disney, Tom; Leigh, Jadwiga; Cooner, Tarsem Singh; Beddoe, Liz
ABSTRACT: Relationship-based practice has become an influential theory through which social work practice is understood. However, much more critical attention needs to be given to the kinds of relationships involved. This paper is based on an ethnographic study of long-term social work that spent 15 months observing practice with service users and organisational life to find out how social workers establish and sustain long-term relationships with children and parents in child protection cases, or don't. The paper introduces into the literature the concept of a 'holding relationship', which was present in several of the cases we studied, especially where therapeutic change occurred. The aims of the paper are to document the nature of a holding relationship and to develop it as a concept. A 'holding relationship' involved social workers being reliable, immersing themselves in the service user's day-to-day existence and developing their life-skills, getting physically and emotionally close to them, and practicing critically by taking account of power and inequalities. The concept of a 'holding relationship' draws on psycho-dynamic and sociological theory to provide new ways of thinking that can help make sense of the practical and emotional relating involved in social work and promote the development of such helpful relationships.